I am in Increasing and Decreasing Functions.
I'm just wondering how to factor this. The original question was y=1/x^2+1, and taking the derrivative i was left with y'=-2x/(x^2+1)^2.
how do i factor the derrivative to get the x's?
I am in Increasing and Decreasing Functions.
I'm just wondering how to factor this. The original question was y=1/x^2+1, and taking the derrivative i was left with y'=-2x/(x^2+1)^2.
how do i factor the derrivative to get the x's?
Well, you can't have division by 0 so concentrate on the numerator.
You have $\displaystyle \frac{-2x}{(x^{2}+1)^{2}}=0$
So, $\displaystyle -2x=0$
Solve for x.
If you want to find inflection points, find y'', set to 0 and solve for x.
$\displaystyle y''=\frac{2(3x^{2}-1)}{(x^{2}+1)^{3}}$
To set this to 0 and solve, just solve $\displaystyle 2(3x^{2}-1)=0$